Human and Professional Sustainable Development by Using the EFI ROM Creative Method. (2015) - Tripon, Avram
Abstract: Elaborated for the human and professional sustainable development of human resources within innovative enterprises by using creative techniques for rendering efficient own activities. A solution for promoting innovative management in the field of human resources in these units is the use of the own original creative method EFI-ROM. It can be applied to selfmanagement and all management hierarchical levels with responsibilities in short, medium and long-term decision. It was tested on the occasion of carrying out some innovative project. In the present paper we present an improved variant and adjusted to the specifics of innovative organizations.